Where Have All the Birds Gone? Essays on the Biology and Conservation of Birds That Migrate to the American Tropics - Terborgh, John (Princeton University Press, 2020)
"Things are going wrong with our environment," writes John Terborgh, "even the parts of it that are nominally protected. If we wait until all the answers are in, we may find ourselves in a much worse predicament than if we had taken notice of the problem earlier. By waiting, one risks being too late; on the other hand, there can be no such thing as being too early." Terborgh's warnings are essential reading for all who care about migratory birds and our natural environment. Why are tropical migrant species disappearing from our forests? Can we save the birds that are left? Terborgh takes a more comprehensive view of migratory birds than is usual--by asking how they spend their lives during the half-year they reside in the tropics. By scrutinizing ill-planned urban and suburban development in the United States and the tropical deforestation of Central and South America, he summarizes our knowledge of the subtle combination of circumstances that is devastating our bird populations. This work is pervaded by Terborgh's love for the thrushes, warblers, vireos, cuckoos, flycatchers, and tanagers that inhabited his family's woodland acreage while he was growing upbirds that no longer live there, in spite of the preservation of those same woods as part of a county park. The book is a tour of topics as varied as ecological monitoring, the plight of the Chesapeake wetlands, the survival struggle of Central American subsistence farmers, and the management of commercial forests